ANALYZING THE WRITING ASSESSMENT TO IMPROVE STUDENTS’ ABILITY IN WRITING PERFORMANCE - Septika Ariyanti; Dyah Fitri Mulati; Defy Gustianing; Eka Pratiwi Yunianti; Bastian, Arif Alexander (Universitas Aisyah Pringsewu, 2023)
A writing assessment is a review of an individual's writing abilities and skills. Usually, the goal is to assess a person's written communication skills. There are numerous various ways to evaluate writing, including essays, performance tasks, and multiple-choice exams. The purpose of a writing evaluation is to thoroughly evaluate an individual's writing abilities, including their command of syntax, vocabulary, style, and organization.The purpose of this research is to analyze the writing assessment of some previous research related for students’ ability in writing. The amount of the research are three research. This research belongs to library research. In collecting the data, the writer use documentation. The instrument used was the writer itself. The data will be analyzed descriptively by use table and words explanation. The result of this research reveals some ways to analyze students’ writing paragraph.